The effect of using artificial intelligence (AI) on students’ critical thinking skills in magnetic electricity courses - Annisa Nur Aini; Himawan Putranta (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2025)
In today’s digital era, AI (Artificial Intelligence) technology has developed rapidly and is being applied in various aspects of life, including education. This study aims to analyze the effect of AI use on students’ critical thinking skills in the electromagnetism course for physics education students who have taken or are currently taking the electromagnetism course. This study employs a quantitative approach, utilizing descriptive analysis. The data collection instrument used in this survey research is a questionnaire. The sampling technique used is simple random sampling. The sample used in the study consisted of 10 respondents from each of the classes of 2021, 2022, and 2023, without any specific provisions or criteria in place. The results of the study indicate that students feel helped by the presence of AI in the learning process. AI technology provides instant solutions to problems and issues, and students can easily access and understand complex material. The findings of this study highlight the need to integrate AI in electromagnetism learning, a complex concept that requires high-level reasoning skills. Initial findings suggest that AI offers benefits, including personalized learning and the visualization of complex ideas, but also presents challenges in terms of teacher preparedness, student digital literacy, and potential technology dependency. Furthermore, students’ low critical thinking skills in electromagnetism emphasize the need for pedagogical innovation. AI is seen as capable of supporting the development of critical thinking through simulations, adaptive assessments, and data-driven guidance. Therefore, empirical research is necessary to determine the extent to which the use of AI improves students’ critical thinking skills.